EFEKTIVITAS DAUN SAMBUNG NYAWA (GYNURA PROCUMBENS) SEBAGAI INSEKTISIDA NABATI PADA LALAT RUMAH - Yolanda E.P.S; marwanto, andriana; Kermelita, Deri (Poltekkes Kemenkes Bengkulu, 2021)
The prevalence of diarrhea in Bengkulu Province handled in 2016 was 12,017 patients, in 2017 it increased to 17,205 patients and in 2018 to 21,313 patients. Whereas according to the Bengkulu City Health Office in 2016 it reached 3,956 patients, in 2017 it increased to 6,202 patients, and in 2018 it became 4,815 patients. This study aims to determine the effectiveness of the gyroscope (Gynura procumbens) leaf extract against home fly mortality. This type of research is quasi-experimental with Post-Test With Control Design with the number of samples used as many as 300 house flies each treatment 25 home flies with 3 repetitions and use three concentrations of leaf extract continued lives (15%, 30%, 45%). Data analysis was performed with univariate and bivariate analysis using the One Way Anova Test. The results showed the number of house fly deaths at a concentration of 15% was 62 heads (82.66%), a concentration of 30% was 65 heads (86.66%) and at a concentration of 45% was 63 heads (84%) and results statistical test known sig value of 1,000 > 0.05, meaning that there is no difference in the average death of house flies between the administration of leaf extracts of concentrations of 15% by 30%, concentrations of 15% by 45% and concentrations of 30% by 45%. Need further research on the utilization of leaf grafting extract as a plant-based insecticide controlling the fly vector by paying attention to the age of house flies.